Scènes de nuit night & architecture : nocturnal exhibition at f'ar Lausanne - May 2019 - Fernández Contreras, Javier 1982-; Kravtchenko, Youri; Portera, Manon (Ediciones Asimétricas, 2021)
SCÈNES DE NUIT explores the role of night in the construction of contemporary cities and societies, illustrating how architectural theory and critique are still associated with sunlight and diurnal paradigms. The exhibition seeks to examine and reflect upon the spaces, activities and media deployed in night culture, using evening events and ephemeral scenography as its main display platform. The five venues SHOP, FILM, CITY, CLUB and FOOD recreate spaces generating practices and night-time rituals on the topics of consumption, film, street, party and food culture, becoming experimental laboratories to focus on and question the relationship between architecture and night. Scènes de Nuit attempts to understand nocturnal spatial phenomena through performative lectures, discussions, walks, meals and screenings
Catalogue of a nocturnal exhibition at f'ar Lausanne held in five different locations: Shop (09.05.2019), Film (12.05.2019), City (18.05.2019), Club (24.05.2019) and Food (29.05.2019)
Keywords: Nacht -- Motiv; Kunst; Ausstellungskatalog -- Forum d'Architectures -- 09.05.2019-29.05.2019 -- Lausanne; Bildband